Pregnancy-Adapted YEARS Algorithm for Diagnosis of Suspected Pulmonary Embolism. Issue 8 (August 2019) - van der Pol, Liselotte M.; Tromeur, Cecile; Bistervels, Ingrid M.; Ni Ainle, Fionnuala; van Bemmel, Thomas; Bertoletti, Laurent; Couturaud, Francis; van Dooren, Yordi P. A.; Elias, Antoine; Faber, Laura M.; Hofstee, Herman M. A.; van der Hulle, Tom; et al.
Abstract : (Abstracted from N Engl J Med 2019;380:1139–1149) Acute pulmonary embolism is one of the leading causes of maternal death, with the overall incidence reported to be 1.72 cases per 1000 deliveries, accounting for approximately 1 death in every 100, 000 deliveries. Since the D-dimer test has low specificity and sensitivity, it is common for pregnant women with suspected pulmonary embolism to undergo computed tomography (CT) pulmonary angiography or ventilation-perfusion (V/Q) scanning, both of which involve radiation exposure to the mother and fetus.